Organic−Inorganic Manganese Bromide Hybrids with Water‐Triggered Luminescence for Rewritable Paper. Issue 4 (17th December 2021) - Liu, Hua‐Li; Ru, Hua‐Yang; Sun, Meng‐En; Wang, Zhao‐Yang; Zang, Shuang‐Quan
Abstract: Stimuli‐responsive luminescent material‐based rewritable paper has received great attention for its potential application in a wide range of areas from anti‐counterfeiting to information encryption. Herein, a photoluminescence (PL) rewritable paper based on an organic metal halide, trans ‐2, 5‐dimethylpiperazine manganese(II) bromide (C6 N2 H16 MnBr4 ) (1), is reported. This 0D organic metal halide hybrid exhibits green emission centered at 548 nm originating from 4 T1 – 6 A1 transition of tetrahedrally coordinated Mn 2+ ions with a PL quantum efficiency of 82%. Interestingly, complex 1 can be transformed into the non‐emissive hydrated phase C6 N2 H16 MnBr4 (H2 O)2 (2) by uptake of coordinating water molecules, wherein Mn 2+ adopts a quasi‐octahedral coordination sphere. The reversible single‐crystal structure transformation between the hydrated and dehydrated phases can switch the PL on and off. Rewritable PL paper has been fabricated by coating complex 1 on filter paper, which exhibits high resolution and excellent "write‐erase‐write" cycle capability. This work presents a new avenue for low‐dimensional lead‐free organic metal halide hybrids toward multilevel information security applications. Abstract : Water molecule‐triggered reversible structural transformation between two organic metal halide hybrids, tetrahedral C6 H16 N2 MnBr4 (1) and octahedral C6 H16 N2 MnBr4 (H2 O)2 (2), accompanied with photoluminescence (PL) on/off has been presented in this work. These heat, vacuum, and moisture‐responsive materials are used to fabricate rewritable paper which shows good resolution and contrast, and great recycling.